Overview Of Vitamin A Supplementation Among Stunted Toddlers In The Working Area Of The Giligenting District Health Center, Sumenep Regency - Indah Nor Faiqoh; Moh. Rusdi; Rizdyana Firmaniar (International Journal of Health Engineering and Technology, 2026)
Stunting is a chronic nutritional problem that remains high in Indonesia, including in Sumenep Regency. Stunting is caused by long-term nutritional deficiencies, recurrent infections, and micronutrient deficiencies, one of which is vitamin A. Vitamin A plays an important role in growth, immune function, and cellular metabolism. This study aimed to describe the administration of vitamin A supplementation among stunted toddlers in the working area of the Gili Genting Community Health Center, Sumenep Regency. This study used a descriptive observational method with a cross-sectional design. The study population consisted of 117 stunted toddlers based on 2024 data, and all were included as the research sample. Data collection was carried out using questionnaires and secondary data obtained from the Community Health Center. Data were analyzed descriptively. The results showed that most stunted toddlers were in the age group of 12–59 months, totaling 69 children, while those aged 6–11 months were 48 children. The highest distribution of stunted toddlers was found in Bringsang Village with 48 children. The coverage of vitamin A supplementation was still not optimal, where only 23.08% of toddlers received vitamin A capsules according to the recommended schedule of twice a year, 35.90% received it less than twice, and 41.03% never received vitamin A supplementation. The conclusion of this study indicates that the coverage of vitamin A supplementation among stunted toddlers in the working area of the Gili Genting Community Health Center is still low. Increased nutrition education for parents, strengthening of posyandu (integrated health service posts), and equitable distribution of vitamin A capsules are needed to support efforts to reduce the prevalence of stunting.